Health sector reform in the Kurdistan Region$1 (BIraq :s financing reform, primary care, and patient safety - Anthony, C. Ross.; Moore, Melinda; Hilborne, Lee H., 1956-; Mulcahy, Andrew; Rand eBooks (Santa Monica, CA : RAND, 2014)
In 2010, the Kurdistan Regional Government asked the RAND Corporation to help guide reform of the health care system in the Kurdistan Region of Iraq. The overarching goal of reform was to help establish a health system that would provide high-quality services efficiently to everyone to prevent, treat, and manage physical and mental illnesses and injuries. This report summarizes the second phase of RAND$1 (Bs work, when researchers analyzed three distinct but intertwined health policy issue areas: development of financing policy, implementation of early primary care recommendations, and evaluation of quality and patient safety. For health financing, the researchers reviewed the relevant literature, explored the issue in discussions with key stakeholders, developed and assessed various policy options, and developed plans or approaches to overcome barriers and achieve stated policy objectives. In the area of primary care, they developed and helped to implement a new management information system. In the area of quality and patient safety, they reviewed relevant literature, discussed issues and options with health leaders, and recommended an approach toward incremental implementation.s
Introduction -- Health Financing Literature -- Health Financing Reform in the Kurdistan Region$1 (BIraq: A Way Forward -- Dual Practice: Options for Dealing with Combined Public and Private Practice Among Physicians -- Primary Care -- Quality and Patient Safety -- Summary and Conclusions.s
"Kurdistan Regional Government."
"Ministry of Planning; Ministry of Health."
"RAND Health."
Includes bibliographical references (p. 95-98).
Also available on the internet via WWW in PDF format.
Description based on print resource.
Keywords: Medical policy -- Iraq -- Kurdistan; Health care reform -- Iraq -- Kurdistan; Medical care -- Iraq -- Kurdistan -- Finance; Primary care (Medicine) -- Iraq -- Kurdistan; Electronic books